2009
DOI: 10.1158/0008-5472.can-08-2467
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2-ERG Gene Fusion Is Not Associated with Outcome in Patients Treated by Prostatectomy

Abstract: A significant number of prostate cancers have been shown to have recurrent chromosomal rearrangements resulting in the fusion of the androgen regulated TMPRSS2 promoter to a member of the ETS transcription factor family, most commonly ERG. This results in ERG overexpression which may have a direct causal role in prostate tumorigenesis or progression. However, the clinical significance of the rearrangement is unclear and, in particular, relationship to outcome has been inconsistent in recent reports. We analyze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
185
5
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(210 citation statements)
references
References 43 publications
(37 reference statements)
16
185
5
4
Order By: Relevance
“…Ten studies reported the prognostic value of the gene fusion in radical prostatectomy (RP) cohorts [19][20][21][22][23][24][25][26][27][28]. In 6 of the 10 studies, TMPRSS2:ERG fusion status was not associated with outcome after surgery [19,21,22,24,27,29].…”
Section: Tmprss2:erg Fusionmentioning
confidence: 99%
“…Ten studies reported the prognostic value of the gene fusion in radical prostatectomy (RP) cohorts [19][20][21][22][23][24][25][26][27][28]. In 6 of the 10 studies, TMPRSS2:ERG fusion status was not associated with outcome after surgery [19,21,22,24,27,29].…”
Section: Tmprss2:erg Fusionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] More recently, several studies demonstrated significant association between ERG rearrangements and PTEN genomic deletions in localized PCA with prognostic implications. [15][16][17][18][19][20] Moreover, studies in transgenic mouse models confirmed that both aberrant expression of ERG and deletion of PTEN are required to develop frank invasive carcinoma, indicating that both genetic aberrations play an important role in driving prostate cancer development and progression. More comprehensive studies are, however required to determine the prognostic significance of these biomarkers for the future clinical management of PCA.…”
Section: Introductionmentioning
confidence: 98%
“…Nam et al 6 found that TMPRSS2-ERG expression was the single most significant predictor of disease relapse after surgery, independent of prostate-specific antigen (PSA) level, tumor grade, and tumor stage. However, Gopalan et al 7 recently reported that TMPRSS2-ERG gene fusion was not associated with tumor pathological stage, biochemical recurrence, metastasis, or with the overall survival of the patient in a study of more than 500 patients. Therefore, the clinical significance of TMPRSS2-ERG gene fusion in prostate cancer remains uncertain.…”
mentioning
confidence: 97%